2018
DOI: 10.1007/s10856-018-6042-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, antibacterial activity in dark and in vitro cytocompatibility of Ag-incorporated TiO2 microspheres with high specific surface area

Abstract: Postoperative infection associated with medical implants is a devastating complication of orthopedic surgery. Considering the difficulties for the diagnosis and treatment of infection, coating the implant material with antibacterial substances is a promising protocol by which to avoid such an adverse reaction. Nanoparticles (NPs) constructed of anatase microspheres, one form of titanium dioxide (TiO), with a high specific surface area are fabricated in this study in a facile one-step process using homogeneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Thus, TiO2 with a specific surface area < 300 m 2 /g was observed most often [19][20][21][22][23]. Values of about 300 m 2 /g were, however, only reported for nanorods and microspheres [24,25], as well as for TiO2-SiO2 composite xerogels [26,27]. Table 1.…”
Section: Nanotube Structure With Pd or Pt Impregnationmentioning
confidence: 99%
“…Thus, TiO2 with a specific surface area < 300 m 2 /g was observed most often [19][20][21][22][23]. Values of about 300 m 2 /g were, however, only reported for nanorods and microspheres [24,25], as well as for TiO2-SiO2 composite xerogels [26,27]. Table 1.…”
Section: Nanotube Structure With Pd or Pt Impregnationmentioning
confidence: 99%
“…Similarly, Ag-TiO 2 systems have been investigated for antimicrobial activities and excellent results have been reported for bacterial disinfection in light/ambient as well as in dark conditions due to the surface plasmon properties of Ag or antibacterial release of Ag ions respectively [ 27 , 40 ]. Weng et al [ 82 ] synthesized the Ag-TiO 2 system with higher surface area which exhibited excellent antibacterial properties against microbes/MC3T3-E1 cells as shown in Fig. 3 A.…”
Section: Tio 2 As Antimicrobial Photocatalystsmentioning
confidence: 99%
“…Different antimicrobial NPs were developed such as Ag [89,90,91,92,93,94,95,96], copper (Cu) [95], ZnO [87,97,98], titanium dioxide (TiO 2 ) [99,100,101] and selenium (Se) [102]. AgNPs showed significant antimicrobial activity against Gram-negative and Gram-positive bacteria [86,103].…”
Section: Antimicrobial Applications In Dentistrymentioning
confidence: 99%
“…A previous study found that the toxicity of NPs had a strong correlation with the time, rather than with the concentration of antimicrobial NPs [19]. A favorable outcome was that the addition of antibacterial NPs made the original materials less toxic but more biocompatible [60,84,90]. In summary, the toxicity of antimicrobial NPs is affected by a variety of factors such as dosage, types, particle size, distribution, duration of action, interaction with other components and so on.…”
Section: Toxicitymentioning
confidence: 99%